Medial plantar and dorsal sural nerve conduction studies increase the sensitivity in the detection of neuropathy in diabetic patients - İŞAK, BARIŞ; ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (ELSEVIER IRELAND LTD, 2008)
objective: Clinical utility of nerve conduction studies (NCS) of the medial plantar and dorsal sural nerves in the early detection of polyneuropathy have already been shown separately. However, at present, there is no data about the combined assessment of these two nerves in distal sensory neuropathy. In the present study, we aimed to evaluate the medial plantar and dorsal sural NCS in a group of diabetic patients with distal sensory neuropathy (DSN) and in healthy controls. Methods: Thirty healthy and 30 diabetic adult patients were included. In all subjects, peripheral motor and sensory NCS were performed bilaterally with surface electrodes on the lower limbs including medial plantar and dorsal sural nerves. In addition, motor and sensory nerves were studied unilaterally on the upper limb. Results: In all patients, nerve action potential (NAP) amplitudes of sural and superficial peroneal nerves were within normal ranges, but in the patient group mean value was significantly lower than in the controls. Among clinically defined 30 DSN patients, medial plantar NAP amplitude was abnormal in 18 (60%) and dorsal sural nerve amplitude was abnormal in 13 (40%) of the patients bilaterally. Additionally, the onset NCV of the dorsal sural nerve was significantly slower in patients than controls (P = 0.038). Evaluation of both of these nerves increased the sensitivity up to 70% in the detection of neuropathy. Conclusions: Bilateral NCS assessment of both of the medial plantar and dorsal sural nerves together increases the rate of diagnosis of diabetic distal sensory neuropathy compared to assessment of either of these nerves. Significance: Assessment of medial plantar in addition to dorsal sural NCS together increases the sensitivity in the detection of neuropathy and allows earlier diagnosis, especially when routine NCS are normal. (c) 2008 International Federation of Clinical Neurophysiology. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: medial plantar nerve; dorsal sural nerve; diabetic sensory neuropathy; SENSORY POLYNEUROPATHY; CLINICAL UTILITY; HEALTHY; FOOT